The influence of demographics on influenza vaccine awareness and hesitancy among adults visiting educational hospital in Saudi Arabia - Abdullah A Alzeer; Lina A. Alfantoukh; Abdulrahman Theneyan; Fawaz Bin Eid; Thamer A Almangour; Abdullah K. Alshememry; Abdulaziz M. Alhossan (Elsevier, 2021)
Objective: To understand the influence of demographics and education levels on awareness levels, and on the prevalence of hesitancy to receive the influenza vaccine among adult patients at King Saud University Medical City (KSUMC). Method: A crosssectional study in the outpatient pharmacy area at KSUMC was conducted. Data was collected from January 1 to January 31, 2020. A total of 318 random adult patients were encountered and a predesigned survey was administered. After capturing demographic information, respondents were categorized into 3 groups: group A consisted of respondents who had never heard of the influenza vaccine; group B was comprised of respondents who answered that they had never received the influenza vaccine; and group C included respondents who answered that they had received at least one influenza vaccine. Results: Out of the 317 survey respondents, 36 (11%) had never heard of the influenza vaccine (Group A). Of the remaining 281 (89%), 122 (39%) had not received the vaccine (Group B), whereas 159 (50%) had received it (Group C). Chi-square test results indicated a significant association between age group and awareness of the vaccine (p = .023). Moreover, there was a significant association between education level and awareness of the vaccine (p = .002). The prevalence of vaccination hesitancy was 42%. Chi-square test results indicated a significant association between gender and vaccination hesitancy (p < .001), and between education level and vaccination hesitancy (p = .011). Conclusion: Influenza vaccination hesitancy is prevalent among the study's population. Further efforts by health care providers and public health services may be necessary to educate the community regarding the influenza vaccine's safety and efficacy.